Estoques de carbono e nitrogênio em Latossolos sob pastagem e ecossistema natural - Eliziario, Daniel Ferreira de Lima (2018)
Changing land use in the conversion of natural ecosystems to pasture causes changes in soil properties and quality. The general objective of this study was to evaluate how conversion of natural ecosystem to pasture affects C and N stock compartments in Latossolos. The study was conducted in the city of Areia-Paraíba, Brazil. Two places were selected, in the first place we had three collection points (two pastures and the reference natural ecosystem) and the second place, two points (one pasture and the reference natural ecosystem). At the sample collection points, a 1 × 1 × 1 m trench was opened where profile samples were collected in the following layers 0-10, 10-20, 20-30, 30-40, 40-60, 60-80 and 80-100 cm, being in these quantified the densities of the soil, the total nitrogen (TN) contents, total organic carbon (TOC), particulate organic carbon (POC), mineral-associated organic carbon (MOC), stock total nitrogen (STN), stock of total organic carbon (STOC), stock of particulate organic carbon (SPOC) and stock mineral-associated organic carbon (SMOC). The data were submitted to the analysis using the Kolmogorov-Smirnov test. To evaluate the differences between the compartments in the soils of the studied environments, the paired Bonferroni 5% test was used. To investigate the differences between the C and N forms in the soil in the layers between the environments and the vertical distribution of C and N at different depths, a two-way ANOVA was used, processed by free software R studio. The conversion of natural ecosystem to pasture affects the carbon and nitrogen stocks and modify their dynamics in the soil, causing changes in the compartments and affecting the addition of organic residues in the soil. Human intervention in natural ecosystems and the implementation of farming systems contribute to the emission of carbon and nitrogen into the atmosphere.